2019
DOI: 10.1002/chem.201805605
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Plutonium Oxide Nanocluster Family to Include {Pu16} and {Pu22}

Abstract: Plutonium(IV) oxide nanoclusters represent an interesting scientific problem regarding structure‐function relationships and are also relevant to global concerns surrounding plutonium reprocessing, the remediation of plutonium‐contaminated soils, and the storage or disposal of plutonium‐containing wastes. Here we report the synthesis of five unique PuIV oxide nanoclusters containing 38, 22, or 16 metal centers and capped only with inorganic ligands, such as chlorine and water, which prevent formation of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 40 publications
2
45
1
Order By: Relevance
“…Mazzanti and Hixon isolated {An 16 } units for U and Pu, respectively, but these clusters differ significantly from those reported by Loiseau et al. due in part to differences in the U IV coordination environment . Still, it remains unclear how the {U 4 } units isolated in this work relate to these larger oligomers and the {U 38 } cluster, in particular.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…Mazzanti and Hixon isolated {An 16 } units for U and Pu, respectively, but these clusters differ significantly from those reported by Loiseau et al. due in part to differences in the U IV coordination environment . Still, it remains unclear how the {U 4 } units isolated in this work relate to these larger oligomers and the {U 38 } cluster, in particular.…”
Section: Resultscontrasting
confidence: 67%
“…For related Pu 38 clusters, Hixon et al. recently proposed that {Pu 16 } and {Pu 22 } are building blocks for Pu 38 , and gas phase studies by Gibson and Haire show evidence for Pu 6 and Pu 16 species . Consistent with this, Loiseau et al.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…[6][7][8][9][10] Them ost debated question is the structural nature of these NPs (crystalline vs.amorphous) as well as the presence of Pu V and other oxidation states in small NPs (< 3nm). [9,[11][12][13][14][15] Va rious studies used different synthetic approaches and different solution conditions to examine aprecipitated product, either amorphous or crystalline.T his has led to ac ontroversy which has not been resolved. Fore xample,W alther et al [14] observed evidence for multiple Pu oxidation states (III, IV,V )i nt he early stages of hydrolysis and polymerization of PuO 2 colloids at pH 0.5-1.0, while Rothe et al [9] reported Pu IV oxyhydroxide-colloid formation.…”
mentioning
confidence: 99%